Collaborative economy, a society service? Involvement with ethics and the common good. Issue 4 (26th April 2021) - Chivite Cebolla, María Peana; Jorge Vázquez, Javier; Chivite Cebolla, Carmen Mª
Abstract: The company at the service of today's society is reinventing itself to satisfy people's needs in a more efficient and adapted way. Globalization and digitization promote increasing interaction and new forms of economic organization such as collaborative economy. However, can it be understood that this new business model, more than others, has as its raison d'être in the search for the "common good"? A first approach suggests the presence of values related to collaboration between equals aiming at a common good. However, the possible existence of a profit motive and the labor relations framework in which certain activities are carried out have created a debate on their ethical qualification. In this context, considering 278 companies in the collaborative economy sector, the relationship between the concept of "common good" and the collaborative economy is analyzed, while examining whether these new realities have an explicit ethical intention (of search for goods for people). According to the results, it is not possible to assert that these platforms have an ethical concern, but it is observed that they are in line with the common good and implicitly contribute to the service of society.